PERAN KEPEMIMPINAN TRANSFORMASIONAL DALAM MENINGKATKAN MUTU MANAJEMEN SEKOLAH DI INDONESIA - Rara Sri Widijastuti (Jurnal Administrasi Pendidikan Indonesia, 2025)
Efforts to improve the quality of education in Indonesia constitute a national strategic agenda; however, international assessment indicators such as the Programme for International Student Assessment (PISA) and the Trends in International Mathematics and Science Study (TIMSS) continue to reveal significant gaps in educational quality. These gaps are closely associated with the quality of school management and the leadership role of school principals, underscoring the importance of strengthening school leadership as a key factor in improving educational quality. This study aims to analyze the role of transformational leadership in enhancing the quality of school management through a review of scholarly literature. The research employs a descriptive literature review conducted systematically by examining reputable national and international journals, academic books, and conference proceedings related to transformational leadership in educational contexts. Data analysis is carried out narratively, focusing on the relationship between transformational leadership and teacher motivation and performance, the strengthening of school organizational culture, the development of instructional innovation, and the enhancement of school management accountability. The findings indicate that principals who implement transformational leadership through inspirational and humanistic approaches reflected in the four core dimensions of transformational leadership, namely idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration are able to enhance teacher motivation and performance, encourage active participation in instructional innovation, strengthen collaborative and productive organizational cultures, and improve accountability and overall school management quality. The practical implications of this study emphasize the importance of developing transformational leadership capacity among school principals through continuous professional development, mentoring programs, and school leadership development policies as strategic approaches to improving the quality of education in Indonesia. Future research is recommended to more deeply integrate local contexts by employing qualitative approaches and mixed-methods research designs to obtain more comprehensive insights.